Approaching the Legal Regime of Consensual Abduction Through History - Adolfo Antonio Díaz-Bautista Cremades (Journal on European History of Law)
Abduction was considered a way to access marriage in the ancient world. Even if it wasn’t lawful, Mythology leaves us traces of this conduct, which was acceptable in Roman society when the kidnapped woman’s consent was present. Constantine, for reasons that we can only suppose harshly prohibited this practice, punishing it with the death of all those involved (even the raped woman). Its regulation went back to the Middle Ages but it was modulated, accepting the remission of the sentence in case of agreement between the parties. This way, a private crime was established in modern times which allowed the woman to take action against the abductor unless they married, thus forcing him to fulfil his marriage promises.